How I do it: optic canal unroofing in surgery for tuberculum sellae meningiomas with compression of the optic nerve - Kozák, J; Bízik, I; Novotný, M; Klener, J (Acta neurochirurgica, 2022)
BACKGROUND: Tuberculum sellae meningiomas are challenging to treat when accompanied with altered vision due to compression of the optic nerve. These tumors mostly refer to be benign; therefore, gross total removal and excellent functional recovery are desired. METHOD: We describe the microsurgical treatment of tuberculum sellae meningioma with altered vision function on the left eye. Intradural unroofing of the optic canal with gross total resection of the tumor led to immediate excellent recovery. Intraoperative video highlights key steps of our surgical approach. CONCLUSION: Optic canal unroofing is in our opinion safe and mandatory when treating tuberculum sellae meningiomas with compression of optic nerve.
Keywords: Optic nerve; Optic canal unroofing; Meningeal Neoplasms; Tuberculum sellae meningioma; Meningioma; Treatment Outcome; Optic Nerve; Sella Turcica; meningeom; meningeální nádory; Retrospective Studies; nádory baze lební; Neurosurgical Procedures; retrospektivní studie; nervus opticus; sella turcica; neurochirurgické výkony; výsledek terapie; lidé; Humans; Recovery of visual functions; Skull Base Neoplasms